2007
DOI: 10.1242/jeb.002337
|View full text |Cite
|
Sign up to set email alerts
|

Humeral retractor EMG during quadrupedal walking in primates

Abstract: The mammalian humeral retractors latissimus dorsi, teres major and caudal parts of the pectoral muscles are commonly thought to contribute to forward impulse during quadrupedal locomotion by pulling the body over the supporting forelimb. While most electromyographic studies on recruitment patterns for these muscles tend to support this functional interpretation, data on muscle use in chimpanzees and vervet monkeys have suggested that the humeral retractors of nonhuman primates are largely inactive during the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 36 publications
1
23
1
1
Order By: Relevance
“…Our findings of a lack of activity in the major forelimb retractor muscles during the support phase conflict with previous recordings from the latissimus dorsi muscle in Virginia opposums (Jenkins and Weijs, 1979), dogs (Tokuriki, 1973;Goslow et al, 1981) and cats (English, 1978). Our results are similar, however, to recordings made from a variety of primates during walking (Larson and Stern, 2007) and to recordings from the pectoralis profundus muscle in a dog made by Tokuriki (Tokuriki, 1973).…”
Section: Pectoralis Profundus and Latissimus Dorsi Musclescontrasting
confidence: 90%
See 1 more Smart Citation
“…Our findings of a lack of activity in the major forelimb retractor muscles during the support phase conflict with previous recordings from the latissimus dorsi muscle in Virginia opposums (Jenkins and Weijs, 1979), dogs (Tokuriki, 1973;Goslow et al, 1981) and cats (English, 1978). Our results are similar, however, to recordings made from a variety of primates during walking (Larson and Stern, 2007) and to recordings from the pectoralis profundus muscle in a dog made by Tokuriki (Tokuriki, 1973).…”
Section: Pectoralis Profundus and Latissimus Dorsi Musclescontrasting
confidence: 90%
“…Several studies have found that the major retractor muscles of the forelimb (pectoralis profundus and latissimus dorsi) are active during the support phase of running steps in Virginia opossums (Jenkins and Weijs, 1979), dogs (Tokuriki, 1973;Goslow et al, 1981) and cats (English, 1978), suggesting that the forelimb does not function as a strut during constant-speed running. The strut hypothesis is supported, however, by electromyograms (EMGs) from the pectoralis profundus muscle of running dogs (Carrier et al, 2006) and a variety of primates during walking (Larson and Stern, 2007), which suggest that the retractor muscles do not contribute to retraction of the forelimb during the support phase.…”
Section: Introductionmentioning
confidence: 99%
“…Cartmill et al, 2002;Demes et al, 1994;Hanna et al, 2006;Kimura et al, 1979;Larson and Stern, 2008;Patel, 2009;Reynolds, 1985;Schmitt et al, 2006;Vilensky, 1983; see also Schmitt, 2003). This research has provided numerous insights into primate evolution.…”
Section: Introductionmentioning
confidence: 99%
“…After the back-stimulation experiments, the free ends of the electrode wires were connected to a 112g, 4-channel, Bio-Sentry Telemetry FM telemetry transmitter, which was then attached to a non-restrictive harness and shirt worn by the subjects (e.g. Larson and Stern, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Boyer et al, 2007;Larson and Stern, 2007;Larson and Stern, 2009;Kingston et al, 2010). Briefly, using a Panasonic 5100HS color video camera with an electronic high-speed shutter, analog video of the subject's behavior was recorded at 60Hz on Fuji SVHS ST-120 videotapes using a Panasonic AG-5210 VCR.…”
Section: Methodsmentioning
confidence: 99%